2020
DOI: 10.1080/14786419.2019.1710701
|View full text |Cite
|
Sign up to set email alerts
|

Verbascoside, synthetic derivatives and other glycosides from Argentinian native plant species as potential antitumoral agents

Abstract: A phytochemical study was performed on three native plant species from the central-western zone of Argentina: Buddleja cordobensis Grisebach, Baccharis salicina Torr. & A. Gray and Nepeta cataria L. We could obtain verbascoside (1) from B. cordobensis. From N. cataria we could obtain 1, 5, 9-epi-deoxyloganic acid (2) L. Finally, we could isolate 2--(L-rhamnopyranosyl)-3-angeloyloxy-15-acetyloxy-7,13( 14)-E-dienent-labdane (3) and 2--(L-rhamnopyranosyl)-3--angeloyloxy-15-hydroxy-7,13( 14)-E-dien-ent-labdane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The HEK 293 cell line was used as non-tumoral control. All cells were incubated at 37 °C in a 5% CO 2 atmosphere and cultured in DMEM media supplemented with 10% fetal bovine serum (FBS), penicillin (10 μg/mL), and streptomycin (100 μg/mL) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HEK 293 cell line was used as non-tumoral control. All cells were incubated at 37 °C in a 5% CO 2 atmosphere and cultured in DMEM media supplemented with 10% fetal bovine serum (FBS), penicillin (10 μg/mL), and streptomycin (100 μg/mL) …”
Section: Methodsmentioning
confidence: 99%
“…All cells were incubated at 37 °C in a 5% CO 2 atmosphere and cultured in DMEM media supplemented with 10% fetal bovine serum (FBS), penicillin (10 μg/mL), and streptomycin (100 μg/mL). 28 4.3.2. Tumoral Cell Proliferation.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…VB has recently received considerable attention owing to its significant clinical value, including antioxidative, antiinflammatory, antibacterial, and antifungal properties (8)(9)(10)(11)(12). Moreover, VB also possesses anti-tumour activity against various cancers, such as glioblastoma, prostate cancer, and breast cancer (13)(14)(15)(16)(17). For example, VB has an anti-tumour role in breast cancer by suppressing cell proliferation (16).…”
Section: Introductionmentioning
confidence: 99%
“…Oleuropein showed potential antioxidant, anti-inflammatory, anti-atherogenic, anti-cancer, anti-viral, anti-aging, and neuroprotective properties [ 10 , 15 , 16 , 17 ]. Verbascoside, also known as acteoside or kusaginin [ 18 ], is a bio-active molecule well-known for its antioxidant, anti-inflammatory, antibacterial, antifungal, potential anticancer, and anti-tuberculosis properties [ 18 , 19 , 20 , 21 , 22 , 23 ]. In a recent study, ligstroside showed beneficial effects against Alzheimer’s disease and the capability in expanding the lifespan and enhancing the cognitive function of aged mice in vivo [ 24 ].…”
Section: Introductionmentioning
confidence: 99%